Acoustic and performance-based ipe wood selection for violin bows - Igor Mottinha Fomin; Thiago Corrêa Freitas; Silvana Nisgoski; Jorge Matos (Maderas: Ciencia y Tecnología, 2025)
Pernambuco wood is the most used material for making professional violin bows. Since the 18th century, it has been known as the best wood for this purpose. However, it is classified as an endangered species. Some researchers looking for alternative woods for bow making have pointed out that ipe wood may have desirable features for making violin bows. Therefore, the objective of this research was to define an evaluation method that could guide selection steps in order to find suitable wood for violin bows testing it in practice. To carry out this research, ipe wood samples were selected from lumber companies and analyzed. Afterward, five violin bows were made and evaluated by professional violinists using a 6-point scale questionnaire. As a result, ipe bows were highly rated by professional violinists, with mean scores spanning 4.21 to 5.10, suggesting a positive level of acceptance. Furthermore, there was a coherence between the scores given by musicians and the estimated potential quality of wood which also had a larger proportion of fibers and lower apparent density, in conformity with other studies. It was concluded that the method adopted worked to find ipe wood suitable for violin bows with characteristics needed to produce professional violin bows even among piles of discarded wood at lumber companies.